Industrial training report: MAB Academy Sdn Bhd / Nur Hanani Amira A Halim - A Halim, Nur Hanani Amira (Universiti Teknologi MARA, Perlis, 2024)
This internship report details my 25-week internship experience at MAB Academy Sdn Bhd in South Support Zone KLIA Selangor, Malaysia, under the Digital & Innovation Learning department. As part of the Bachelor of Business Administration (Hons) in Human Resources Management program, this internship provided me with valuable exposure to the real-world work environment and equipped me with essential professional skills and knowledge. Throughout my internship, my primary responsibility was to manage Multimedia Workshop project which involve the whole MAB Academy staffs. This involved overseeing the entire process, from brainstorming new ideas to ensuring its successful identified the creativity problem among instructors. This experience allowed me to apply my knowledge on strategy management to practical scenarios and gain a deeper understanding of the industry. In addition to the practical skills I acquired, the internship also played a significant role in my personal development. I learned to become more mature, responsible, and professional in my approach to work. Through interactions with colleagues and top management, I enhanced my communication and interpersonal skills, fostering a sense of teamwork and collaboration. Overall, my internship at MAB Academy it not only provided me with a deeper understanding of the working profession but also contributed to my personal growth and development. I am grateful for the opportunity to have been a part of the MAB Academy team and for the knowledge and skills I gained during my time there.